Audiovisual strategies to foster listening comprehension process in students of the 7th grade at Beatriz Miranda de Cabal High School, 2017 - Ortíz, Hannia Massiel; De Gracia, Edward (David, Panamá : UDELAS, 2017)
The project use the strategies for the development of listening comprehension arises from the need to increase the level of knowledge and understanding in the area of english in the institution, because due to the lack of documents and the lack of educational curriculum.
Table of Content Contenido Chapter 1 Chapter II : Theoretical framework 2.1. Audiovisual strategies to foster listening comprehension 2.1.1. Characteristics 2.1.2. Advantages 2.1.3. Appliication of the videos in the listening process 2.1.4. The use of voice recording tools to foster listening comprehesion 2.1.5.The use of songs in the development of english listen comprehension 2.1.6. The use of movies and short films to foster listening comprehension 2.1.7. The use of audiobooks to foster listening comprehension 2.2. Theories that support listening comprenhension 2.2.1. The complementarity of listening and viewing 2.2.2. Essential features of the listening process 2.2.3. Visual and paralinguistic support 2.2.4.1. Information organization 2.2.4.2. Familiarity of topic 2.2.4.3. Explicitness 2.2.4.4. Type of input 2.3. Elements that interfere with the process of oral comprehension in students 2.3.1. Cultural differences 2.3.2. Accent 2.3.3. Length and speed of listening 2.3.4. Lack of motivation 2.4. Stages of listening comprehension process of the english language in studentis 2.5. Types of listening 2.5.1. Extensive listening 2.5.2. Inensive listening Chapter III. Methodological aspects Chapter IV. Analysis of results Conclusions Recomendation References
Incluye Table of Content
Documento presentado para optar por el Título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- LANGUAGE; MATERIALES AUDIOVISUALES -- TESIS DE LICENCIATURA; INGLÉS -- TESIS DE LICENCIATURA; FACULTAD DE EDUCACIÓN ESPECIAL Y PEDAGOGÍA; ESCUELA DE PEDAGOGPIA; LICENCIATURA EN DOCENCIA EN INGLÉS; BEATRIZ MIRANDA DE CABAL HIGH SCHOOL